Afghanistan - Public Sector Accounting and Auditing : A Comparison to International Standards - World Bank (Washington, DC, 2012)
This assessment of public sector accounting and auditing is generally meant to help implement more effective public financial management (PFM) through better quality accounting and public audit processes in Afghanistan and to provide greater stimulus for more cost-effective outcomes of government spending. More specific objectives are (a) to provide the country's accounting and audit authorities and other interested stakeholders with a common firmly based knowledge as to where local practices stand in accordance with international standards of financial reporting and auditing; (b) to assess the prevailing variances; (c) to chart paths for improving the accordance with international standards; and (d) to provide a continuing basis for measuring improvements. The study has taken the international standards as axiomatic with any acceptable options incorporated in the standards. The study has not assessed whether the country should adopt a limited version of the standards, as the processes of developing the standards have already considered any acceptable options that can be incorporated into the text of the standards, but they do not override authoritative national standards issued by governments, regulatory or professional accounting bodies.